Notas sobre a arquitetura rural paulista do segundo século” e a capela do sitio Santo Antônio. Imprecisões - Sombra Junior, Fausto Barreira (Risco - Journal of Architecture and Urbanism, 2014)
Since 1944, the student Luis Saia, while still being the technical assistant of the Sphan’s 6th Region, starts a professional period of intense practical and theoretical production relates to a group of rural houses known as “casas grandes dos arredores de São Paulo”. During this process stands out the interventions in the sítio Santo Antônio’s chapel (in São Roque) and the preparation of the article “Notas sobre a arquitetura rural paulista do segundo século”. Both these works, analysed from a close point of view, will lead us to the discovery of subtle imprecisions.